The Art of Narrative Distortion: Manipulating Time, Space, and Psyche in Poe’s Short Stories - Aryal, Anusuya (Journal of Innovation in Academia, 2025)
This study explores the narrative techniques of unreliable narration in Edgar Allan Poe’s short stories “Ligeia”, “The Pit and the Pendulum,” and “Manuscript Found in a Bottle.” It investigates how Poe’s narrators distort time, space, and psychological perception to construct narrative ambiguity and disorientation amongst the readers. Drawing upon Wayne C. Booth’s theory of rhetorical narration and Gerard Genette’s narrative structural analysis, this study demonstrates that Poe’s narrators do not just merely mislead readers but rather actively immerse them in psychological disorientation and narrative ambiguity. Ultimately, Poe’s strategic use of unreliable narration emerges not as a narrative flaw but as a deliberate technique that deepens thematic complexity and reinforces Gothic conventions of instability and uncertainty. The findings contribute to broader discussions on the evolution of unreliable narration in psychological and Gothic fiction and reaffirm Poe’s pioneering role in shaping modern narrative practices.